The Effects of Fecal Microbiota Transplantation on the Symptoms and the Duodenal Neurogenin 3, Musashi 1, and Enteroendocrine Cells in Patients With Diarrhea-Predominant Irritable Bowel Syndrome - Mazzawi, Tarek; El-Salhy, Magdy; Lied, Gülen Arslan; Hausken, Trygve (Frontiers in Cellular and Infection Microbiology, 2021)
Introduction Interactions between gut microbiota and enteroendocrine cells play important role in irritable bowel syndrome (IBS). Reduced stem cells densities and their differentiation into enteroendocrine cells may cause abnormal densities of the duodenal enteroendocrine cells in IBS patients. Materials and methods We aimed to investigate the effects of fecal microbiota transplantation (FMT) on stem cells differentiation into enteroendocrine cells as detected by neurogenin 3, stem cells as detected by Musashi 1 and the enteroendocrine cells in the duodenum of IBS patients. The study included 16 IBS patients according to Rome III criteria. Four patients were excluded. The remaining patients (n=12, 4 females and 8 males) were divided according to the cause of IBS into post-infectious (n=6) and idiopathic (n=6) IBS. They completed the following questionnaires before and 3 weeks after FMT: IBS-Symptom Severity Scoring system (IBS-SSS) and IBS-Symptom Questionnaire (IBS-SQ). Feces donated from healthy relatives of the patients were transplanted via gastroscope. Biopsies were taken from the descending part of the duodenum at baseline and 3 weeks after FMT. They were immunostained for neurogenin 3, Musashi 1 and all types of duodenal enteroendocrine cells, and quantified by computerized image analysis. Microbiota analyses of feces collected just before and 3 weeks after FMT were performed using GA-mapTM Dysbiosis test (Genetic Analysis AS, Oslo, Norway). Results The total scores for IBS-SSS and IBS-SQ were significantly improved 3 weeks after receiving FMT, P=0.0009 and <0.0001, respectively. The stem cell densities of neurogenin 3 increased significantly following FMT (P=0.0006) but not for Musashi 1 (P=0.42). The cell densities of chromogranin A, cholecystokinin, gastric inhibitory peptide, serotonin and somatostatin, but not for secretin, have significantly changed in both IBS groups after 3 weeks from receiving FMT. Conclusion More than two-thirds of IBS patients experienced improvement in their symptoms parallel to changes in the enteroendocrine cells densities 3 weeks after FMT. The changes in the enteroendocrine cells densities do not appear to be caused by changes in the stem cells or their early progenitors rather by changes in the differentiation progeny as detected by neurogenin 3. The study was retrospectively registered on at ClinicalTrials.gov (ID: NCT03333291).